The searching for agents for Alzheimer's disease treatment via the system of self-consistent models - Toropov, Andrey A; Toropova, Alla P; Achary, P Ganga Raju; Raškova, Maria; Raška, Ivan (Toxicology mechanisms and methods, 2022)
Robust quantitative structure-activity relationships (QSARs) for hBACE-1 inhibitors (pIC50) for a large database (n = 1706) are established. New statistical criteria of the predictive potential of models are suggested and tested. These criteria are the index of ideality of correlation (IIC) and the correlation intensity index (CII). The system of self-consistent models is a new approach to validate the predictive potential of QSAR-models. The statistical quality of models obtained using the CORAL software (http://www.insilico.eu/coral) for the validation sets is characterized by the average determination coefficient R2v= 0.923, and RMSE = 0.345. Three new promising molecular structures which can become inhibitors hBACE-1 are suggested.
Keywords: Software; Quantitative Structure-Activity Relationship; Molecular Structure; Monte Carlo Method; software; Alzheimer's disease; kvantitativní vztahy mezi strukturou a aktivitou; metoda Monte Carlo; hBACE-1; index of ideality of correlation; Humans; lidé; Alzheimer Disease; CORAL software; correlation intensity index; Alzheimerova nemoc; QSAR; molekulární struktura